The influence of english on syntactic structure in Indonesian: a case study of digital advertising - Sitompul, Monika Sales; Sihombing, Maslan M.R.; Fitri, Aida (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
The use of English in digital advertising in Indonesia is increasingly widespread as a result of globalization and modern marketing strategies, but this phenomenon raises questions about its influence on Indonesian syntactic structure and communication effectiveness. This study aims to analyze how English affects the syntactic structure and discourse in digital advertisements and its impact on marketing communication strategies. Using syntax and discourse analysis methods, this study analyzed 50 digital ads from various platforms, which were purposively selected based on industry categories. The results show that English influences word order, phrase usage and sentence structure in digital ads, creating hybrid patterns that are more concise and persuasive. In terms of discourse, English is used to reflect modernity and global appeal, although it sometimes creates a comprehension gap for certain local audiences. The implications of this study emphasize the importance of balance in the use of language blends to remain linguistically and strategically effective, as well as culturally relevant. This study contributes to the development of applied linguistics literature and provides insights for marketing practitioners in designing optimal communications.